Understanding the influence of community characteristics on wellness for rural older adults: A meta-synthesis. (June 2016) - Winterton, Rachel; Warburton, Jeni; Keating, Norah; Petersen, Maree; Berg, Turi; Wilson, Jill
Abstract: This review identifies how diverse rural community characteristics interact to influence older adults' capacity to achieve wellness. Through a meta-synthesis of the academic literature, an ecological model is developed which classifies environmental determinants of individual wellness for rural older adults in terms of their proximity to the individual. Findings demonstrate that socio-spatial and resource environments play a key role in influencing wellness for rural older adults through fostering and developing individual opportunities and capabilities, promoting positive perceptions of the environment, and in contributing to objective and subjective indicators of health and wellbeing. This is achieved in two distinct ways: indirectly through interactions between the socio-spatial and resource environments, and directly through interactions between the individual and their socio-spatial or resource environments. In addition to contributing to the emerging literature on wellness and rural ageing, this review provides a clearer understanding of how rurality and community interact at different levels to facilitate outcomes for older adults. Highlights: Wellness for rural seniors is influenced by socio-spatial and resource environments. These environments act directly and indirectly on rural seniors to foster wellness. Wellness reflects the ability of environments to foster opportunity and capability. It also reflects positive perceptions of environments, health and wellbeing.